ISCHEMIC STROKE ANTERIOR AND POSTERIOR CIRCULATION : CHARACTERISTIC COMPARISON AND RISK FACTORS IN KANDOU CENTRAL HOSPITAL MANADO PATIENTS - Andika Surya Atmadja; Hugo Dwiputra; Mieke A.H.N Kembuan; Finny Warouw (Jurnal Sinaps, 2021)
Background: Ischemic stroke occurs more frequent in anterior than posterior circulation. Ischemic stroke has some risk factors, but the difference between anterior and posterior circulation risk factors still lack of study. Methods: This study was performed in Kandou Central Hospital Manado by collecting the data retrospectively during year 2020. The data was classified to ischemic stroke anterior or posterior circulation. We also collect the patient’s data include gender, age, smoking habit, and also performed physical and supporting examination. Result: There was 100 patients with ischemic stroke anterior circulation and 21 patients with ischemic stroke posterior circulation. The mean age of both group was same (60 years old), but posterior circulation has a wider range of age. Ischemic stroke anterior circulation was more common in man, while posterior circulation was more common in woman. Our data shows 42% ischemic stroke anterior circulation and 33,3% ischemic stroke posterior circulation patients are smoker. The most common risk factor for both group was same, that was hypertension and the second most common was high LDL level. The most frequent heart disease in stroke was arrythmia especially in anterior circulation. Discussion: Ischemic stroke was more frequent in anterior circulation. There was no different in patients characteristics between these two groups. The most common risk factors in both groups was hypertension, and the second most frequent was high LDL level. The most frequent heart disease in stroke patient was arrythmia, especially in anterior circulation. There was no significant differences by statistic between ischemic stroke between anterior and posterior circulation.